Analisis Karakteristik Morfologi Famili Poaceae (Gramineae) di Kawasan Lembuak Kebon, Kecamatan Narmada Kabupaten Lombok Barat - Khairunnisa Al Izzati; M. Harja Efendi; Nining Purwati (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2024)
The purpose of this mini research is to find out the various types or species and morphology of the family Poaceae (Gramineae) ranging from grasses to bambo and corn. The method used in this mini research is random sampling technique, where random sampling technique is a random sampling of the family Paceae (Gramineae) found in the selected area. Mini research was carried out by exploring the location of the plantation and collecting information about the existence of plant species of the Poaceae family found in the Lembuak Kebon village area. Poaceae family plants are identified by matching morphological characters using various literature such as books, journals, and websites. Tools and materials used in mini research activities are stationery, rulers, meters, and smartphone cameras to record and document the types of Poaceae family plants found. Data analysis presented descriptively consists of roots, stems, leaves, flowers, and seeds of Poaceae family plants. mini research and observations that have been carried out on Sunday, May 26, 2024 in the Lembuak Kebon area, Narmada sub-district, West Lombok, there are 8 species from the Poaceae (Gramineae) family which are included in angiosperms, namely: Pennisetum purpureum, Panicum maximum, Cynodon dactylon, Eleusine indica, Zea mays, Panicum dichotomiflorum, Oplismenus undulatifolius, and Gigantochloa apus.